High ecosystem service delivery potential of small woodlands in agricultural landscapes. Issue 1 (1st December 2019) - Valdés, Alicia; Lenoir, Jonathan; De Frenne, Pieter; Andrieu, Emilie; Brunet, Jörg; Chabrerie, Olivier; Cousins, Sara A. O.; Deconchat, Marc; De Smedt, Pallieter; Diekmann, Martin; Ehrmann, Steffen; Gallet‐Moron, Emilie; et al.
Abstract: Global forest loss and fragmentation have strongly increased the frequency of forest patches smaller than a few hectares. Little is known about the biodiversity and ecosystem service supply potential of such small woodlands in comparison to larger forests. As it is widely recognized that high biodiversity levels increase ecosystem functionality and the delivery of multiple ecosystem services, small, isolated woodlands are expected to have a lower potential for ecosystem service delivery than large forests hosting more species. We collected data on the diversity of six taxonomic groups covering invertebrates, plants and fungi, and on the supply potential of five ecosystem services and one disservice within 224 woodlands distributed across temperate Europe. We related their ability to simultaneously provide multiple ecosystem services (multiservice delivery potential) at different performance levels to biodiversity of all studied taxonomic groups (multidiversity), forest patch size and age, as well as habitat availability and connectivity within the landscape, while accounting for macroclimate, soil properties and forest structure. Unexpectedly, despite their lower multidiversity, smaller woodlands had the potential to deliver multiple services at higher performance levels per area than larger woodlands of similar age, probably due to positive edge effects on the supply potential of several ecosystem services. Biodiversity only affected multiservice delivery potential at a low performance level as well as some individual ecosystem services. The importance of other drivers of ecosystem service supply potential by small woodlands in agricultural landscapes also depended on the level of performance and varied with the individual ecosystem service considered. Synthesis and applications . Large, ancient woodlands host high levels of biodiversity and can therefore deliver a number of ecosystem services. In contrast, smaller woodlands in agricultural landscapes, especially ancient woodlands, have a higher potential to deliver multiple ecosystem services on a per area basis. Despite their important contribution to agricultural landscape multifunctionality, small woodlands are not currently considered by public policies. There is thus an urgent need for targeted policy instruments to ensure their adequate management and future conservation in order to either achieve multiservice delivery at high levels or to maximize the delivery of specific ecosystem services. Abstract : Above, one of the small woodlands included in the study in Belgium (photo by Pieter De Frenne). Below, diagram of a piecewise structural equation model linking the environment, biodiversity and high‐performance multiservice delivery potential in small woodlands across Europe (blue arrows indicate positive effects and red arrows indicate negative effects). Multidiversity was highest in large and ancient forest patches, but multiservice delivery potential at high performance levels per area was maximal in the smallest and most ancient woodlands and was not affected by multidiversity. Editor's Choice